1997
DOI: 10.3168/jds.s0022-0302(97)76138-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Identification of Bifidogenic Growth Stimulator Produced by Propionibacterium freudenreichii

Abstract: A bifidogenic growth stimulator produced by Propionibacterium freudenreichii was purified, and its chemical structure was determined. We obtained 7.1 mg of a bifidogenic growth stimulator from 1738 g of lyophilized P. freudenreichii cells by silica gel column chromatography, Sephadex LH-20 column chromatography, and preparative HPLC. The mass of the bifidogenic growth stimulator was 217.037 (C11H7NO4) as determined by high resolution mass spectrometry. Various experimental analyses indicated that the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 13 publications
2
48
0
1
Order By: Relevance
“…It has been reported that Propionibacterium freudenreichii produces large amounts of tetrahydromenaquinone-9 (MK-9 (4H)) and the precursor 1,4-dyhidroxy-2-naphtoicacid (DHNA) which is a known bifidogenic factor [110][111][112]. In order to improve the production of these metabolites, different laboratory culture protocols that could be applied to an industrial scale have been assayed finding out that DHNA production is markedly influenced by carbon source limitation and the oxygen supply.…”
Section: Nutraceuticals Production: Cla Vitamins Eps and Trehalosementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that Propionibacterium freudenreichii produces large amounts of tetrahydromenaquinone-9 (MK-9 (4H)) and the precursor 1,4-dyhidroxy-2-naphtoicacid (DHNA) which is a known bifidogenic factor [110][111][112]. In order to improve the production of these metabolites, different laboratory culture protocols that could be applied to an industrial scale have been assayed finding out that DHNA production is markedly influenced by carbon source limitation and the oxygen supply.…”
Section: Nutraceuticals Production: Cla Vitamins Eps and Trehalosementioning
confidence: 99%
“…This property has been demonstrated both in vitro [110,111,178,179], and in vivo [127,[180][181][182] and the bifidogenic growth stimulators (BGS) involved in this effect were identified. The active compounds that were present in supernatants of P. freudenreichii, P. jensenii and P.…”
Section: Gut Microbial Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They could thus be useful to prevent lactose intolerance. It has also been demonstrated that these bacteria favour the growth of bifidobacteria, both in vitro [20] and in the human intestine [3]. It is noteworthy that some strains of dairy propionibacteria produce bacteriocins.…”
Section: Introductionmentioning
confidence: 99%
“…One of the identified active bifidogenic factors is 2-amino-3-carboxy-1,4-napthoquinone produced by a P. freudenreichii strain. Stimulation of growth of Bifidobacterium was observed both after the addition of the compound to the growth medium as well as during the mixed cultivation of the producer strain with bifidobacteria [8]. Several features of Propionibacterium strains suggest that they can be used as probiotic microflora.…”
Section: Introductionmentioning
confidence: 99%